SUPERVISI AKADEMIK SEBAGAI UPAYA UNTUK MENINGKATKAN KETERAMPILAN MENGAJAR GURU PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI SEKOLAH DASAR DI KOTA BINJAI - Ikhsanti Hannum (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
This paper describes the enhancement of the teacher's ability to carry out the learning process, after academic supervision. The method used for research is qualitative with quantitative data collection and analysis techniques, and Classroom Action Research approach. The number of teachers used as a sample was 20 people, and the results obtained showed that after the research was carried out, in the first cycle a total of 76 samples which were further divided based on 8 assessment criteria (47.5%) had increased their abilities, while in cycle II, as many A total of 139 samples divided into 8 assessment criteria (86.8%) increased their teaching ability. This data shows the achievement of the successful implementation of academic supervision of supervisors of teachers.Keywords: PAIBP, Performance, Academic Supervision